EPIPHANY: A STYLISTIC-SEMIOTIC INTERPRETATION OFJAMES JOYCE'S ARABY - Mohammed, RaedFadhil (International Journal of Psychosocial Rehabilitation, 2020)
This study is a stylistic-semiotic scrutiny of the literary text as a communicative occurrence.Its applicable area is James Joyce's epiphany as represented in his short story,Araby. Being an informative unit, the text is not a haphazard set of linguistic units; it is a systematic structure governed by a definite set of formal relations. So to be communicative, the text should meet certain criteria, without which there is no human communication. This paper purports to investigate the seven standards of textuality in James Joyce's Arabic in terms of de Beaugranda and Dresselr's model, paying much attention to the basic concepts of cohesion and coherence in Joyce's story. The model is encoded in their book, Introduction to Text Linguistics (1981). Out of 15 short stories in Joyce’s Dubliners (1972), Araby will be selected for text analysis. The paper aims at unraveling how the seven standards of textuality operate to build up the mental world of the story and how these forms operate to produce the text as a communicative occurrence. What is new about this paper is the attempt to approach Joyce’s language of narrative and how to produce the vision of Ireland in given special and temporal circumstances by using a new way of analysis, i.e., the stylistic-semiotic approach (henceforth SSA). The stylistic-semiotic approach is the study of the narrative text in context; it attempts to analyze the literary text not only as a system of interrelated signs but as a product of a given culture. Every human product is a message that communicates a certain world view through specific verbal signs in a specific cultural code. While the structural relations underlying the narrative structure are universal, the narrative sequential methodologies follow culturally specific principles. The study construes two interlinked circles: the first concerns the theoretical grid, while the second deals with the stylistic-semiotic analysis. The study is rounded up with concluding remarks elicited from the study quest.